2019
DOI: 10.1136/bmjopen-2019-030316
|View full text |Cite
|
Sign up to set email alerts
|

Integration of traditional and complementary medicine into medical school curricula: a survey among medical students in Makerere University, Uganda

Abstract: ObjectiveTo describe the disposition and sociodemographic characteristics of medical students associated with inclusion of traditional and complementary medicine in medical school curricula in Uganda.DesignA cross-sectional study conducted during May 2017. A pretested questionnaire was used to collect data. Disposition to include principles of traditional and complementary medicine into medical school curricula was determined as proportion and associated factors determined through multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
0
22
2
1
Order By: Relevance
“…Values and beliefs regarding religion, politics, and health affect the use of traditional treatment among individuals. [15] It is important that health professionals know different approaches as they are the ones to moderate TCAM practices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Values and beliefs regarding religion, politics, and health affect the use of traditional treatment among individuals. [15] It is important that health professionals know different approaches as they are the ones to moderate TCAM practices.…”
Section: Resultsmentioning
confidence: 99%
“…[11,13] A study conducted at a university in the United Arab Emirates found the rate of TCAM users as 34%, whereas another study from Uganda found that 59% of the participants used TCAM. [14,15] The rate of TCAM use varies from country to country and even in different regions of the same country.…”
Section: As Seen Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Internacionalmente, tratamentos não-convencionais, medicina alternativa e complementar (CAM), tratamentos espirituais complementares e congêneres crescem em aceitação e interesse de pesquisa entre médicos e estudantes de medicina em países tão diversos como Alemanha, China, Paquistão, Uganda, Palestina e Arábia Saudita (Münstedt, Harren, Georgi e Kackethal, 2011;Song e Tang, 2017;Ashraf et al, 2019;Mwaka et al, 2019;Ahmad et al, 2019;Khan et al, 2020).…”
Section: Discussionunclassified